PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MACFROMEDIA FLASH 8 PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS V SEKOLAH DASAR - Al Gafur, Muhammad Zainal Abidin; Listyarini, Ikha (TAMAN CENDEKIA: Jurnal Pendidikan Ke-SD-an, 2018)
The underlying reason that triggersthe researcher to conduct this study is the lack of facilities and lack of media so that it is initiated to overcome the learning shortagein class to be an interactive learning that is not in the form of paper based learning considered to be not alive and monotonous.The problems that is analysed in this research is how do media development establish interactive learning to overcome the learning shortage by using Macromedia Flash 8 so that it is able to be a media of learning on the social subjects for students of fifth grade in primary school? The purpose of the research is to find out the steps in developing Macromedia Flash 8 to be implemented in learning process to fill out the shortage of learning in SD N 02 Mranggen, Demak. This is a research and development research. The population of the research is all students in SD N 02 Mranggen, Demak academic year of 2017/2018. The sample of the research is 33 students of fifth grade. The technique of data collection uses the scale of Likert and Guttman. The data of the research is obtained through the observation and other economic indicators. The propose future design of this research is the development of the interactive learning by utilizing the advance support of Macromedia Flash 8 that is created. According to the freedom on learning material designing for social subject, it is worthwhile to implement this learning model to fifth grade students in the second semester under the curriculum of school (KTSP Curriculum). The validation process is carried out in two ways, include validation from media experts which shows the result of 90.5% with two categories are considered to be very good and validation from material designer experts showing the result of 85 % with two categories are considered to be very good. According to the research result, it is recommended to develop and implement the interactive media by using Macromedia Flash 8 as one of the alternative media in classroom teaching and learning process.